Resurgence of scabies in Italy: The new life of an old disease - Antonio Laganà; Ilaria Saia; Giovanni Genovese; Giuseppa Visalli; Giuseppa D'Andrea; Salvatore Sidoti; Angela Di Pietro; Alessio Facciolà (Parasite Epidemiology and Control)
Scabies, an old parasitic disease with a worldwide presence, has witnessed a recent resurgence in many parts of the world even in the light of the COVID-19 pandemic. We conducted a study on this resurgence in the Italian province of Messina, Sicily, evaluating the general features of affected people to better understand the possible modes of transmission. Specifically, we considered all the scabies notifications made in the period 2003–2022. Then, we focused on those cases occurred in the three-years period 2020–2022 carrying out an active surveillance by calling patients and asking them questions about their recent habits and movements and their consequent chances of contracting the disease. In total, 935 cases of scabies were reported from 2003 to 2022, with a remarkable increase between 2020 and 2022, when 288 cases were reported. Of these patients, we were able to reach by phone 240 (83.3 %) and interview them. Students were the most affected group (24.1 %), followed by retirees (21.0 %) and healthcare workers (13.2 %). Unfortunately, concerning the possible mode of transmission, more than half (58.5 %) of patients were not able to understand the real source of their infection. When known, the most common ways of transmission were a familiar origin (10.7 %) followed by causes linked to health environments (nursing home stays and hospital admissions). Moreover, 66.9 % of all the reported cases were part of an outbreak. Larger outbreaks occurred in healthcare facilities for more than half of the cases (69.4 %), the majority of which (88.9 %) were in nursing homes. Our research confirms the resurgence of scabies in our territory similar to trends in other European countries. Some critical factors, including the COVID-19 pandemic, probably played a key role in influencing this epidemiological trend and showed the importance of always monitoring the epidemiology of all notifiable diseases to enable prompt action by competent authorities to limit their spread to the community.